ECG Classification Using Knn And LDA for Continuous Heart Monitoring - Ocneanu, Adrian; Jones, Colin; Adler, Andy (CMBES Proceedings, 2013)
In this work, an ECG data representation and encoding schema is investigated. Its aim is to support mobile and continuous heart monitoring, for athletes and cardio-vascular disease (CVD) patients. For data analysis and encoding, a linear discriminant analysis (LDA) was performed on ECG data capturing several heart conditions, obtained from PhysioNet. On-line performance, in terms of classification of unknown heartbeats, using k-nearest neighbours (kNN), was computed and reported. We show that such an approach allows for simple, well-established, and robust data classification tools to be deployed. Using this representation schema, we hypothesize there is a potential for cheaper and more user- friendly apparatuses in the market.